Applying Impact Assessment to Protect Workers’ Privacy in Intelligent Monitoring - Wang, Qi; Tan, Zelin (International Journal of Social Sciences and Public Administration, 2025)
In the context of the artificial intelligence era, the application of workplace intelligent monitoring technology improves management efficiency while posing a threat to workers’ personal information security. This article analyzes the conflict between workers’ personal information rights and the management rights of employers, and points out the inadequacies of existing laws in protecting workers’ personal information. To address this challenge, the article proposes introducing Personal Information Protection Impact Assessment (PIPIA), aimed at improving transparency in information processing and workers’ participation, while emphasizing the importance of the purpose limitation principle in monitoring activities. In response to the challenges in implementing PIPIA, the article suggests strategies such as refining assessment standards, improving labor laws, and strengthening the construction of supervisory departments, aiming to find a balance between intelligent monitoring and personal information protection.